Modeling and robust decentralized control for speed-up phase of web processing systems for composite elastic web. Issue 11 (July 2020) - Chu, Xiaoyan; Nian, Xiaohong; Fu, Xinran; Wang, Haibo; Xiong, Hongyun
Highlights: It is the first time that a nonlinear physical model of web processing systems with two unwinders is established, which contains modeling of compounding and lamination process. The system time-varying or uncertain parameters are regarded as interval variables, based on which the web processing system is considered as an interval system. Then, the problem of tension control is transformed into the problem of robust control for interval system. For the speed-up phase of each subsystem, the variation dynamic model and equilibrium control inputs are obtained firstly, and then the problem of tension control for web processing systems is converted into the asymptotically stability of variation system. A robust decentralized controller is designed for variation system, and then the control inputs of web processing system are obtained by multiplying the designed control compensation and the equilibrium control inputs. Abstract: The web processing system for composite elastic web contains two unwinders and a compounding processing, which is used for transporting two various webs to form a kind of composite web with desirable properties. The physical properties of the web materials before and after compounding will undergo essential changes, and the motion characteristics of compounding roll shaft and the web tension are more complicated than the common systems, which makes it challenging to establish the physical model. In this study, a physical model is firstly established based on the general physical laws. Then, the variation dynamic model of web processing systems is built under the speed-up situation by Taylor expansion. Next, the method of interval matrix is introduced to deal with the problem of wide-range variation of radius and inertia of the unwinding/rewinding roller, parameter uncertainties and production speed changes. Subsequently, the web processing system is taken as an interval system, based on which a robust decentralized controller is proposed. Sufficient conditions of the existence of the proposed controller are obtained based on Lyapunov theory. Finally, the simulations are performed on a five-motor driven system and the results illustrate that the proposed method is effective and can improve the control performance.